Optimization of Production Capacity using a Dynamic System Approach at Food Company - Dwi Sukma Donoriyanto; Nur Rahmawati (Future Science, 2022)
The current competition in the food industry encourage companies to be able to produce products that are diverse, in a good quality, and in a timely manner to meet the company's production targets. PT XYZ is a food company in Indonesia. To be able to meet production targets, companies must adjust their production capacity by utilizing their workforce. However, the problem is that there are so many variables involved in the system so that the problem becomes more complex and hard to solve. Therefore in this study, a dynamic system approach is used to be able to see the interactions between variables in the system using Vensim software. Based on the research that has been done, the values ??of E1 < 6% and E2 < 2.5% indicated that the data used in this research is valid in other words the model used has represented the real system conditions. From the research, the best result is to gradually increase the installed capacity so that there is no over production occured. Using this scenario, the availability of raw materials for is 5901 boxes.